William Blount papers - Blount, William, 1749-1800.; Blount, Thomas, 1759-1812.; Blount, Willie, 1768-1835.; Miller, Pleasant Moorman, -1849.
Correspondence and documents relating to Blount's activities as a speculator in the Old Southwest from the 1780s to the period following the Blount conspiracy of 1797 and to his career as governor of the Tennessee territory and superintendent of the U.S. Southern Indian Dept. (1790-1796) and as U.S. senator from Tennessee (1796-1797). Includes papers (1803-1823) of Thomas and Willie Blount and Pleasant Moorman Miller. Correspondents include David Allison, Thomas Hart, Benjamin Hawkins, Robert Hays, John Haywood, James S. Holland, Andrew Jackson, Wyly Martin, Andrew Pickens, James Robertson, John Sevier, John Steele, and Hugh Williamson.
Microfilm edition available
Microfilm from originals in the Manuscript Division.
Delegate to the Continental Congress from North Carolina, U.S. senator from and governor of Tennessee, and superintendent of the U.S. Southern Indian Dept.
Collection material in English.
Keywords: Allison, David -- Correspondence; Hart, Thomas, -- -1808 -- Correspondence; Hawkins, Benjamin, -- 1754-1816 -- Correspondence; Hays, Robert -- Correspondence; Haywood, John, -- 1762-1826 -- Correspondence; Holland, James, -- 1754-1823 -- Correspondence; Jackson, Andrew, -- 1767-1845 -- Correspondence; Martin, Wyly -- Correspondence; Pickens, Andrew, -- 1739-1817 -- Correspondence; Robertson, James, -- 1742-1814 -- Correspondence; Sevier, John, -- 1745-1815 -- Correspondence; Steele, John, -- 1764-1815 -- Correspondence; Williamson, Hugh, -- 1735-1819 -- Correspondence; United States. -- Southern Indian Department; Indians of North America -- Government relations; Land speculation -- Southwest, Old; Tennessee -- Politics and government -- To 1865.; Delegates, U.S. Continental Congress -- North Carolina; Governors -- Tennessee; Indian agents; Senators, U.S. Congress -- Tennessee